Randomized Clinical Trial of a Prenatal Breastfeeding and Mental Health Mixed Management Intervention. (November 2021) - Zhao, Ying; Lin, Qiping; Zhu, Xinli; Wang, Jing
Background: The continuity of maternal depressive symptoms throughout the perinatal period and breastfeeding problems have adverse influences on breastfeeding. Research aim: To compare the feeding patterns and breastfeeding experiences, maternal health and mental health, and breastfeeding self-efficacy between women with depressive symptoms who participated in a prenatal individualized mixed management intervention and those who received usual care. Methods: Chinese primigravida ( N = 182) with an Edinburgh Postnatal Depression Scale score ≥ 9 in late pregnancy (≥ 28 weeks and < 35 weeks) were randomly assigned to the intervention group ( n = 84) or the control group ( n = 84). Intervention group participants received four sessions of individualized mixed management combining psycho-education and breastfeeding education. Breastfeeding self-efficacy, feeding patterns, maternal depression, and health status were evaluated in both groups. Results: Significant differences were noted between the groups in breastfeeding self-efficacy at 42 days postpartum ( p < .05) and feeding patterns at 3 months and 6 months postpartum ( p < .05). Repeated measures analysis of variance showed significant differences in the EPDS scores between groups at three postpartum time points ( p < .05). The intervention group had significantly lower postpartum depression as diagnosed by the MINI ( p < .05). Conclusions: A prenatal individualized mixed management intervention holds promise as an effective prevention and health promotion program addressing breastfeeding outcomes and maternal mental health. This RCT was registered (ChiCTR-IOR-17013761) with Chinese Clinical Trial Registry, http://www.chictr.org.cn/enIndex.aspx on 12/7/2017.